2014
DOI: 10.1111/vop.12213
|View full text |Cite
|
Sign up to set email alerts
|

The eye of the red‐eared slider turtle: morphologic observations and reference values for selected ophthalmic diagnostic tests

Abstract: Normal parameters found for the ocular diagnostic tests were: esthesiometry: 5.84 ± 0.48 cm; IOP: 5.42 ± 1.70 mmHg; CCT: 154.5 ± 0.14 μm; palpebral fissure length: 9.71 ± 0.55 mm; modified Schirmer tear test: 2.55 ± 3.4 mm; globe axial length: 7.60 ± 0.23 mm; anterior chamber depth: 0.76 ± 0.23 mm; lens axial length: 2.45 ± 0.28 mm; vitreous chamber depth: 4.31 ± 0.42 mm. An avascular retinal pattern with nerve fibers radiating from the small white circular optic disk was observed. None of the animals had a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 47 publications
6
17
0
Order By: Relevance
“…Bacillus spp. are commonly isolated in reptiles (Somma et al 2015) and in dogs (Meekins et al 2015b). Although there was a higher prevalence of Gram-positives, corroborating the findings of Bayón et al (2007), Escherichia coli accounted for 6.1% of the observed bacterial flora, higher than usually described but as frequently as bacteria isolated from the eyes of owls (Asio clamator) (Rodarte-Almeida et al 2013) and flamingos (Meekins et al 2015a).…”
Section: Discussionsupporting
confidence: 84%
“…Bacillus spp. are commonly isolated in reptiles (Somma et al 2015) and in dogs (Meekins et al 2015b). Although there was a higher prevalence of Gram-positives, corroborating the findings of Bayón et al (2007), Escherichia coli accounted for 6.1% of the observed bacterial flora, higher than usually described but as frequently as bacteria isolated from the eyes of owls (Asio clamator) (Rodarte-Almeida et al 2013) and flamingos (Meekins et al 2015a).…”
Section: Discussionsupporting
confidence: 84%
“…Normal conjunctival flora has been described in chelonians such as turtles and tortoises . Previous studies in sea turtles have reported conjunctival bacterial flora in sick animals .…”
Section: Discussionmentioning
confidence: 99%
“…Culture of the microorganisms was performed using Petri dishes with 6% sheep blood agar, eosin methylene blue agar, and tryptose broth. Dishes were incubated at 37°C in an aerobic environment for 24‐48 hours for identification of the mesophilic bacteria (growth range between 25‐40°C) . After growth, the colonies were identified based on the presence or absence of hemolysis on blood agar, and morphological and biochemical characteristics according to routine laboratory techniques (catalase test, oxidation‐fermentation test, coagulase test, oxidase test, methyl red test, motility test, triple sugar iron, indole production, Simmons citrate agar, urease, malonate, and carbohydrate fermentation: glucose, sucrose, lactose, mannitol, adonitol, arabinose, and dulcitol) .…”
Section: Methodsmentioning
confidence: 99%
“…Given the difficulties described for the use of the STT strip (Willis & Wilkie 1999, Müller et al 2010, Beckwith--Cohen et al 2015 or even mSTT strip (Williams 2012, Kern & Colitz 2013, Somma et al 2015, Meekins et al 2015, some authors suggest the use of the phenol red test (Willis & Wilkie 1999, Kern & Colitz 2013, Beckwith-Cohen et al 2015. Although this test is well tolerated by birds (Bliss et al 2015), low reproducibility has been reported in large Psitacciformes (Holt et al 2006), and better PRT reproducibility on A. ventralis (Storey et al 2009).…”
Section: Discussionmentioning
confidence: 99%